Social protection for men and women in the Philippines: Some insights for improving program design of social insurance schemes - Celia M. Reyes; Aubrey D. Tabuga; Ronina D. Asis (Philippine Institute for Development Studies (PIDS), 2018)
To reduce the risks and vulnerability to sudden income shocks faced by households due to natural calamities, disability, illnesses and other causes, ensuring that social protection programs are designed in a relevant and effective manner is crucial. This study examines the coverage of several social protection programs with focus on social insurance schemes like the SSS/GSIS, PhilHealth and social pension programs. The idea is to profile those with access to these schemes, examine potential exclusion issues and leakages, and provide insights for improving access to insurance schemes. This paper likewise examines access to social insurance with a gender perspective to help determine any need for differentiated intervention or program design for men and women.
Keywords: 330; Social protection; Philippines; social insurance; gender